Likeable social media : how to delight your customers, create an irresistible brand, and be generally amazing on all social networks that matter - Kerpen, Dave; Greenbaum, Michelle; Berk, Robert E., 1923- (McGraw-Hill Education, 2019)
Harness the power of social media to attract new customers and transform your business!More than three billion people are now on social media. If you're not in the social media marketing game, you're not in the game at all. From one of the world's leading figures in the world of social media marketing, Likeable Social Media reveals everything you need to know about building your brand and attracting & retaining loyal customers through smart, savvy social media engagement. This updated edition of the bestselling classic is packed with expert advice and new case studies that demonstrate the latest best practices. You'll find critical information about new and relevant social media platforms, such as Snapchat, along with updated tools, and tactics around video, mobile, paid media, and data; and need-to-know insights into existing platforms/content, including Instagram, LinkedIn and Facebook stories. Likeable Social Media shows you how to: *Engage customers and crowdsource innovation online *Create content that resonates with consumers and provides value *Integrate social media into the entire customer experience *Effectively deal with criticism and negative feedback on social media *Grow your audience across social channels, and much more.